Elasticities of Gasoline Demand in Switzerland - Baranzini, Andrea; Weber, Sylvain (My University, 2013)
Using cointegration techniques, we investigate the determinants of gasoline demand in Switzerland over the period 1970–2008. We obtain a very weak price elasticity of −0.09 in the short run and −0.34 in the long run. For fuel demand, i.e. gasoline plus diesel, the corresponding price elasticities are −0.08 and −0.27. Our rich dataset allows working with quarterly data and with more explicative variables than usual in this literature. In addition to the traditional price and income variables, we account for variables like vehicle stocks, fuel prices in neighbouring countries, oil shocks and fuel taxes. All of these additional variables are found to be significant determinants of demand.
Keywords: Gasoline demand; Elasticities; Error correction model.